Molecular identification and characterization of biofilm-forming microbial communities from Lake Palakpakin in a fixed-bed bioreactor wastewater treatment system - BAGONOC, REJ (Archīum Ateneo, 2018)
Lake Palakpakin of San Pablo City, Laguna is a water resource affected by anthropogenic activities through aquaculture and sewage effluents from lakeshore communities. In a previous study, a laboratory-scale fixed-bed bioreactor (FBBR) supplied with lakewater sample was observed to degrade organophosphate flame retardants (OPFRs) such as tris (2-butoxyethyl) phosphate (TBEP). However, the microorganisms responsible for biodegradation are still unknown. Thus, this study aimed to identify and characterize microbial communities from the lake in an FBBR setting, compare changes in microbial structure and composition in response to TBEP supplementation, and isolate and identify possible OPFR-degrading microorganisms from the FBBR. PCR-DGGE analysis revealed that the dominant bacterial groups in the FBBR include Cyanobacteria, Betaproteobacteria, and Bacteroidetes. Dominant fungal groups in the FBBR include Glomerales, Archaeosporales, Tremellales and Hypocreales. Upon TBEP supplementation, bacterial diversity decreased while fungal diversity increased. Betaproteobacteria and Acidobacteria from the bacterial community, and Tremellales and Hypocreales from the fungal community, increased in abundance. Eight fungal isolates were obtained from the FBBR through culture-dependent techniques. Isolates 1, 2.1, 2.2, 2.3, 3, and 4 belonged to genus Acremonium, being closely related to Acremonium sp. J-11. Isolates 5 and 6 belonged to genus Trichoderma, and were identified as T. asperellum strain QT22043 and T. asperellum strain ITS B1902, respectively. The capability of the isolates to grow on minimal media supplemented with TBEP, as well as their associations with organophosphate pesticide degradation in previous studies, suggest that these isolates are capable of degrading different kinds of organophosphate compounds.